On the robustness of the Single-Edge-Precracked-Beam (SEPB) method for fracture toughness testing of ceramic materials - Schellenberger, Anja; Belli, Renan; Karsten, Jürgen; Lohbauer, Ulrich (Engineering Fracture Mechanics, 2023)
The Single-Edge-Precracked-Beam (SEPB) method for the testing of fracture toughness (KIc) of ceramic materials is a variation of the Single-Edge-Cracked-Beam (SEPB) method for the test of metallic materials that creates a sharp precrack not by fatigue, but by a “bridge indentation” technique that induces a crack to pop-in under compression loading. This precrack is sharp and overcomes the issue of blunt notch-root radii resulting from the Single-Edge-V-Notched-Beam (SEVNB) method, which overestimates the KIc of ceramics with submicrometric microstructures. However, the difficulties in obtaining a valid precrack and measurement make of the SEPB a low-yield, time- and cost-intensive method. Here we evaluate the SEPB method using large datasets of two fine dental grade ceramics to assess the sensitivity of the validity criteria in ISO 15732 and ASTM C 1421 and the effect of their violations in the obtained KIc. We compile datasets including or excluding validity criteria and combine those of the two standards to establish their effect on the mean and scatter of the data. We discuss the appropriateness of the validity ranges and of some criteria as a whole, while arguing for tightening the criterion precrack frontline asymmetry and for the dropping of criteria regulating the extent of stable crack extension.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Ceramics; Fracture mechanics; Fracture toughness; Lithium disilicate; Single-Edge-Precracked-Beam; Zirconia